ANALISA TERHADAP SISTEM PENGENDALIAN INTERNAL PENERIMAAN DAN PENGELUARAN KAS (Studi Pada Rumah Pemotongan Hewan Kota Malang) - Sari, Lilik Indah Permata; Hariadi, Bambang (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
Abstract: In conjunction with the increasing complexity of financial transactions in a company, the escalating business competition requires the management to have comprehensive supervision of the entire flow of the company's transactions. One of the financial instruments majorly influencing financial statements, cash has different characteristics from other assets: difficult ownership identification, transferable, small in size, and highly desirable. To avoid cash misappropriation, an accounting control system of cash receipts and disbursements is required in a precise and systematic manner. This study aims to determine how the company applies the accounting system of cash receipts and disbursements and whether the elements of internal control have been implemented in both systems. This study is analyzed descriptively utilizing a qualitative approach involving primary and secondary data collected from interviews, observations, and documentation in the Regional Slaughterhouse Company of Malang City. The results of this study revealed that the Regional Slaughterhouse Company of Malang City has relatively properly implemented an accounting system of cash receipts and disbursements despite some weaknesses such as double accounting recording tasks conducted by the treasurer, cash receipts (BKM) made by the cash receipts treasurer, the cash disbursements (BKK) made by the cash disbursement treasurer, and the absence of cash insurance on hand and cash in transit insurance.